2014
DOI: 10.1002/jcp.24576
|View full text |Cite
|
Sign up to set email alerts
|

Reelin/DAB‐1 Signaling in the Embryonic Limb Regulates the Chondrogenic Differentiation of Digit Mesodermal Progenitors

Abstract: Reelin is a bioactive component of some extracellular matrices. Most studies on this signaling glycoprotein have been performed in the developing nervous system, where Reelin binds to the very-low-density lipoprotein receptor (VLDLR) and apolipoprotein E receptor 2 (ApoER2) of target cells. This induces phosphorylation of the intracellular adaptor protein Disabled-1 (Dab-1), which subsequently activates downstream effectors to regulate important aspects of neuroblast biology. Here, we show that the components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
(72 reference statements)
0
21
0
Order By: Relevance
“…Reelin and Dab1 are expressed in the undifferentiated limb mesoderm, and their levels decrease before interdigital cell death, which is necessary for digit formation (Díaz‐Mendoza et al, ). The reelin receptors ApoER2 and Vldlr are also expressed in the developing limb cartilage and tendons (Díaz‐Mendoza et al, ).…”
Section: Reelin Signaling In the Development Of Non‐neuronal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reelin and Dab1 are expressed in the undifferentiated limb mesoderm, and their levels decrease before interdigital cell death, which is necessary for digit formation (Díaz‐Mendoza et al, ). The reelin receptors ApoER2 and Vldlr are also expressed in the developing limb cartilage and tendons (Díaz‐Mendoza et al, ).…”
Section: Reelin Signaling In the Development Of Non‐neuronal Tissuesmentioning
confidence: 99%
“…Analysis of the reelin signaling pathway components in micromass cultures of limb skeletogenic progenitors by quantitative PCR showed that levels of reelin, Dab1 and ApoER2 decrease as the cartilage undergoes differentiation, while expression of Vldlr follows the opposite pattern (Díaz‐Mendoza et al, ). Reelin expression in the limb is up‐regulated in response to FGF2, a cell survival factor, and down‐regulated in response to bone morphogenetic protein 7 (BMP7), which induces apoptosis (Díaz‐Mendoza et al, ). Dab1 silencing in micromass cultures reduced chondrogenesis and induced cell death, with decreased phosphorylation of Akt and lower levels of focal adhesion kinase (Díaz‐Mendoza et al, ).…”
Section: Reelin Signaling In the Development Of Non‐neuronal Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified a number of non-neuronal functions for reelin [812]. For example, reelin signaling was found to regulate the homeostasis of the intestinal crypt-villus unit [11], formation of thrombin clots [10], and to be important for establishment of the lymphatic vasculature [12].…”
Section: Introductionmentioning
confidence: 99%
“…A member of the sine oculis homeobox (SIX) transcription factor family, SIX2, acts as a marker of nephronic progenitor cell self-renewal and plays a pivotal role in the growth process of cartilage, pyloric sphincter, eyes, tendon germ cells, craniofacial system, and cerebrum [4][5][6][7][8][9]. SIX2 is ubiquitously present throughout the development of the genitourinary system, including nephrogenic cord and metanephros [10][11][12].…”
Section: Introductionmentioning
confidence: 99%